Mberu, a new neurigonine genus from southeastern Brazil (Diptera: Dolichopodidae) - Capellari, Renato Soares; de Souza Amorim, Dalton (Zootaxa, 2011)
A new genus of Dolichopodidae with modified wing venation both in males and females is described from the Atlantic Forest in southeastern Brazil, Mberu pepocatu gen. nov. et sp. nov. The species is described and illustrated in detail, including the male and female terminalia. The systematic position of Mberu is considered and the genus is assigned to the tribe Coeloglutini of Neurigoninae, possibly closely related to Coeloglutus Aldrich and Neotonnoiria Robinson.